Integration of Mental and Behavioral Health in Pediatric Health Care Clinics. (November 2017) - Hansel, Tonya; Rohrer, Glenn; Osofsky, Joy; Osofsky, Howard; Arthur, Elizabeth; Barker, Chikira
Abstract : Objective: Integrating behavioral health services into primary and pediatric health care settings is important to increase availability and access to quality mental and behavioral health care for children and adolescents. The Mental and Behavioral Health Capacity Project implemented models of pediatric integrated health care at Federally Qualified Health Clinics covering largely rural communities in Louisiana and impacted communities on the Florida Panhandle. The objectives of this article are to describe the programs and demonstrate sustainability and effectiveness of services provided. Design: A subsample from the Louisiana clinics collected data at intake and follow-up at 1, 3, and 6-month intervals. The hypotheses were that child behavior problems and parenting stress would significantly decrease over the course of treatment. Setting: This study was conducted at 2 Federally Qualified Health Clinics in rural southeast Louisiana that provide pediatric primary health care. Participants: Sample parameters were child patients younger than 18 years presenting at primary health care clinics in Southeast Louisiana (N = 177); the mean age was 9.8 years (standard deviation = 4.3 years). Intervention: Brief behavioral health services included parental education, medication management, stress management, empowerment, and psychodynamic interventions. Main Outcome Measure: The main outcome measures were the Pediatric Symptom Checklist and the Parenting Stress Index. Results: Statistically significant decreases in child behavior problems and parenting stress were revealed, with 87% reporting satisfaction with services. Conclusions: Utilizing community-based and culturally sensitive approaches, mental and behavioral health integrated into pediatric health care clinics can be sustainable and effective at improving child behavior problems, parenting stress, and overall family functioning.